As Metamorfoses de Helena nas Tragédias de Eurípides (Século V a.C.) - SILVA, Tatielly Fernandes (2012)
The present Dissertation aims to understand the many representations of the mythic character Helen, as they have been elaborated by the tragedian Euripides. Selected as sources for this research, three tragedies shall be analysed in our work: The Trojan Women (415 AD), Orestes (408 AD) , and Helen (412 AD). Whenever it may come necessary, we will use the other tragedies as supporting documents to the subject we are attending to endorse, for which we may appeal also to the works of Homer, Hesiod and the sophist Gorgias of Leontini, as well as the plays of other great tragedians from the Classical Athens, Aeschylus and Sophocles. By the utilization of the concept representation , which have been largely discussed by most historians in the last decades of 20th century, we will be intending to make an association between representation and other common concepts used by the New Social History, such as memory and mythology. This is due to the multiple understanding we can achieve over the character Helen as a mytheme as it is presented both in narrative and interpretations in the Greek mythological system as it was known in the Classical Athens. The image of Helen was reinterpreted by Euripides tragedy, mainly because Helen s Pan-Hellenic characteristics, which were determinant for the tragedian s work as a ideal condition guaranteed by its eminent poetic/narrative style. By reinventing his Helens, Euripides has increased through the tragic mimesis a particular representation which was intertwined with the mythic traditions and the poetical and philosophical view of his contemporaries.